DILEMMAS FACING NURSING HOMES AND ASSISTED LIVING PROVIDERS DURING HURRICANES. (11th November 2018) - Hyer, K; Dosa, D; Peterson, L; June, J; Jester, D; Dobbs, D; Thomas, K
Abstract: Emergency planning for vulnerable populations constitutes a major element of disaster preparedness and is an area in which guidance and policy remains controversial. Residents of long term care facilities are especially vulnerable, as they comprise a subpopulation with medical comorbidities such as dementia and significant custodial needs. Over 24, 000 nursing home and assisted living residents were evacuated from Texas and Florida facilities during Hurricanes Harvey and Irma. We present the experiences of 303 Florida nursing homes and 1830 assisted living centers who detail the problems of sheltering in place, including electrical power loss, families evacuating residents, and multiple evacuations as the storm changed direction and projected path. The difficulties of evacuating residents highlight the dilemmas facing administrators and emergency management personnel as they make the decision to shelter in place or evacuate in the face of major hurricanes.